If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3Y + -2Z = -5 Solving 3Y + -2Z = -5 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '2Z' to each side of the equation. 3Y + -2Z + 2Z = -5 + 2Z Combine like terms: -2Z + 2Z = 0 3Y + 0 = -5 + 2Z 3Y = -5 + 2Z Divide each side by '3'. Y = -1.666666667 + 0.6666666667Z Simplifying Y = -1.666666667 + 0.6666666667Z
| 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax | | 4x-9=ax-3 | | 54-12x=16x+10 | | (0.6*2x)+(0.4*x)=6 | | X^2+y^2=6z |